RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI KERITING (Capsicum annuum L.) TERHADAP PEMBERIAN PUPUK NPK 16-16-16 DAN PUPUK KANDANG LEMBU - Novilda Elizabeth Mustamu (UNIVERSITAS LABUHANBATU, 2019)
The method used is a randomized block design (RBD) with 12 factorial combinations of treatments and 3 replications, Pearl 16-16-16 NPK factor consists of 4 levels, namely: N0 = Without treatment, N1 = 10 g / plant, N2 = 15 g / plant, N3 = 20 g / plant, while Cow Manure factor consists of 3 levels ie: L0 = Without treatment, L1 = 1 kg / plant, L2 = 1.5 kg / plant. There are 4 parameters observed, namely plant height (cm), stem diameter (mm), weight of the fruit crop sample (g), and perplot fruit weight (g).The results showed that treatment NPK 16-16-16 Pearl significant effect parameters to heavy crop of fruit samples, and heavy fruit perplot while no real influence on the parameters of plant height and stem diameter. Cow Manure treatment showed a significant influence on plant height parameters, but there is also a significant effect on the parameters of the sample weight and the weight of fruit planting fruit perplot. While there was no significant effect on the parameters of trunk diameter. Interaction between NPK Fertilizer and Cow manure did not give the significant effect on all parameters were observed. Keywords : NPK Fertilizer, Cow manure, Capsicum annuum L